Road Tolling and Domestic Revenue Mobilisation in Zimbabwe - Chilunjika, Alouis; Uwizeyimana, Dominique E.; Chilunjika, Sharon R. T. (International Journal of Economics and Financial Issues, 2023)
The study analyses the effectiveness of road tolling-systems as an instrument for mobilising domestic revenue in Zimbabwe. The study assessed the effectiveness of road-tolling systems in mobilising revenue to recoup the costs of building, operating and maintaining road infrastructure. Revenue performance was rated using the internal and external dimensions of toll revenue, which revolve around activities such as toll revenue collection, administration (remittance) as well as the Zimbabwe National Road Administration’s (ZINARA’s) distribution and usage of the toll revenue. By way of mixed methods research design, the study conceptualised and contextualised the theory, models, technologies and practices of toll revenue collection in Zimbabwe. The study found that the Zimbabwean road tolling model as a hybrid conventional tolling model is a progressive, effective and reliable tool to raise revenue for constructing road infrastructure and related road-related capital investments in Zimbabwe and that the internal toll revenue performance is up-to-date with reduced toll revenue leakages and increased toll revenue yield. However, the study found that there is no meaningful investment on the road network and related highway infrastructure thus making the performance of external toll revenue questionable. The study recommended the strengthening of toll revenue collection, management, remittance and toll fees usage.